Alpha‐Synuclein is Involved in DYT1 Dystonia Striatal Synaptic Dysfunction. Issue 5 (14th April 2022) - Ponterio, Giulia; Faustini, Gaia; El Atiallah, Ilham; Sciamanna, Giuseppe; Meringolo, Maria; Tassone, Annalisa; Imbriani, Paola; Cerri, Silvia; Martella, Giuseppina; Bonsi, Paola; Bellucci, Arianna; Pisani, Antonio
Abstract: Background: The neuronal protein alpha‐synuclein (α‐Syn) is crucially involved in Parkinson's disease pathophysiology. Intriguingly, torsinA (TA), the protein causative of DYT1 dystonia, has been found to accumulate in Lewy bodies and to interact with α‐Syn. Both proteins act as molecular chaperones and control synaptic machinery. Despite such evidence, the role of α‐Syn in dystonia has never been investigated. Objective: We explored whether α‐Syn and N‐ethylmaleimide sensitive fusion attachment protein receptor proteins (SNAREs), that are known to be modulated by α‐Syn, may be involved in DYT1 dystonia synaptic dysfunction. Methods: We used electrophysiological and biochemical techniques to study synaptic alterations in the dorsal striatum of the Tor1a + / Δgag mouse model of DYT1 dystonia. Results: In the Tor1a +/Δgag DYT1 mutant mice, we found a significant reduction of α‐Syn levels in whole striata, mainly involving glutamatergic corticostriatal terminals. Strikingly, the striatal levels of the vesicular SNARE VAMP‐2, a direct α‐Syn interactor, and of the transmembrane SNARE synaptosome‐associated protein 23 (SNAP‐23), that promotes glutamate synaptic vesicles release, were markedly decreased in mutant mice. Moreover, we detected an impairment of miniature glutamatergic postsynaptic currents (mEPSCs) recorded from striatal spiny neurons, in parallel with a decreased asynchronous release obtained by measuring quantal EPSCs (qEPSCs), which highlight a robust alteration in release probability. Finally, we also observed a significant reduction of TA striatal expression in α‐Syn null mice. Conclusions: Our data demonstrate an unprecedented relationship between TA and α‐Syn, and reveal that α‐Syn and SNAREs alterations characterize the synaptic dysfunction underlying DYT1 dystonia. © 2022 The Authors. Movement Disorders published by Wiley Periodicals LLC on behalf of International Parkinson Movement Disorder Society.